Severe Human Intestinal Spirochetosis: An Unusual Cause of Diffuse Colonic Ulcerations in a Patient Living with HIV - T. A. Ajose; J. Aniekwena; V. S. Effoe; M. Simien (Case Reports in Gastrointestinal Medicine)
We describe a case of a homosexual male with human immunodeficiency virus (HIV) and CD4 count of 246 presenting with acute severe bloody diarrhea. Infectious work up was negative, and colonoscopy revealed severe diffuse colonic ulcerations. Histopathologic analysis and Treponemal pallidum immunostaining confirmed the diagnosis of intestinal spirochetosis. There was no evidence of co-infection with other pathogens. His symptoms completely resolved after a 14-day course of metronidazole. This case is notable as colonic ulceration of any severity in patients living with HIV is rarely identified with intestinal spirochetosis. Hence, it should be considered in the differential diagnosis of colonic ulcerations.